A Comparison of the Maximum Deviation Measured in Intermittent Exotropia Using Various Clinical Conditions. Issue 2 (3rd April 2019) - Algee, Kailee; Walsh, Leah; Hahn, Erik
ABSTRACT: Background and Purpose : In the Intermittent Exotropia (IXT) population determining the largest deviation for surgical planning has been suggested for desired surgical outcomes Throughout the literature, the clinical tests that elicit largest deviation remains unclear. Patients and Methods : 24 IXT subjects were measured at the customary 1/3 m and 6 m fixation, with +3D lenses at 1/3 m, at far distance (20 m), 1/3 m and 6 m after PMO, with +3D lenses at 1/3 m after PMO, and far distance (20 m) after PMO, in an attempt to determine which of these conditions elicit the largest exodeviation. Results : At near, all subjects had clinically significant increases with at least one condition. In 87.5%, clinical and statistical increases occurred with +3D lenses and/or with +3D after PMO. There was no statistically significant difference between those conditions. At distance, 16.7% demonstrated clinically significant increases. Two increased at 20 m and 6 m after PMO similarly, and all increased at 20 m fixation with or without PMO, without a significant difference between measurements at 20 m and 20 m after PMO. All increases at 20m, with and without PMO were statistically significant. Conclusion : This research indicates that measurements with +3D lenses and at 20 m are the most efficient for the maximum deviation in IXT patients.